Effects of acetic acid on the total viable counts of microbes and overall acceptability of dressed broiler meat (University Journal of Zoology, Rajshahi University, 2013)
This study was conducted to evaluate efficacy of acetic acid solution to eliminate pathogens, prevent food deterioration and extend the shelf-life of dressed broiler meat without adversely affecting its quality. A total of 40 broilers were categorized into two groups. Each group was further categorized into two sub-groups: one for intact skin and another for without skin. Each bird of either group viz. comprised of two portions breast and thigh muscle. Acid spray and acid immersion were used. Bacteriological analysis by total viable count (TVC) and sanitary quality determination of dressed broiler by taste panel scores were performed. Acetic acid treatment reduced the initial level of TVC by about 0.5 to 0.724 log colony forming unit (CFU)/gm of meat. Maximum reduction in TVC (0.724) was achieved when acetic acid immersion treatment was given to meat and it was evident that the meat quality of dressed broiler after treatment with acetic acid remains better up to 5 days of storage.DOI: http://dx.doi.org/10.3329/ujzru.v31i0.15370Univ. j. zool. Rajshahi Univ. Vol. 31, 2012 pp. 01-04